Pevonedistat, a NEDD8‐activating enzyme inhibitor, induces apoptosis and augments efficacy of chemotherapy and small molecule inhibitors in pre‐clinical models of diffuse large B‐cell lymphoma. Issue 1 (9th April 2020) - Torka, Pallawi; Mavis, Cory; Kothari, Shalin; Belliotti, Sarah; Gu, Juan; Sundaram, Suchitra; Barth, Matthew; Hernandez‐Ilizaliturri, Francisco J.
Abstract: We studied the biological activity of pevonedistat, a first‐in‐class NEDD8‐activating enzyme (NAE) inhibitor, in combination with various cytotoxic chemotherapy agents and small molecule inhibitors in lymphoma preclinical models. Pevonedistat induced cell death in activated B‐cell (ABC) diffuse large B‐cell lymphoma (DLBCL) cell lines and to a lesser degree in germinal center B‐cell (GCB) DLBCL cell lines. In pevonedistat sensitive cells, we observed inhibition of NF‐κB activity by p65 co‐localization studies, decreased expression of BCL‐2/Bcl‐XL, and upregulation of BAK levels. Pevonedistat enhanced the activity of cytarabine, cisplatin, doxorubicin, and etoposide in ABC‐, but not in the GCB‐DLBCL cell lines. It also exhibited synergy with ibrutinib, selinexor, venetoclax, and A‐1331852 (a novel BCL‐XL inhibitor). In vivo, the combination of pevonedistat and ibrutinib or pevonedistat and cytarabine prolonged survival in SCID mice xenograft models when compared with monotherapy controls. Our data suggest that targeting the neddylation pathway in DLBCL is a viable therapeutic strategy and support further clinical studies of pevonedistat as a single agent or in combination with chemotherapy or novel targeted agents.